Corporate Governance Rules in Six Stock Exchanges: A Comparative Study - Ching, Hong Yuh; Tardelli, Renan (Advances in Social Sciences Research Journal, 2015)
This paper aims to compare the corporate governance rules around the world and to ascertain which Stock Exchange SE is more adherent to our proposed corporate governance framework. The SE researched were Tokyo TSE, New York NYSE, Frankfurt Stock Exchange, Brazil BM&FBovespa, London Stock Exchange and Toronto TSX. Several governance models or frameworks extracted from the literature were analyzed, however the integration across these studies showed extremely difficult. This lead us to build our own “proxy” framework composed of 15 rules. TSX has the lowest corporate governance standard compared to other five SE because its document does not provide description in 12 rules out of 15, while London has the highest corporate governance standard with detailed description in 11 rules. As more and more companies do business around the world with their counterparts and governments, it becomes increasingly important to understand the similarities and differences between the corporate governance rules and practices in some Stock Exchange around the world.